Managing Friends and Foes: Sanctioning Mutualists in Mixed‐Infection Nodules Trades off With Defense Against Antagonists - Camille E. Wendlandt; Saumik Basu; Angeliqua P. Montoya; Paige Roberts; Justin D. Stewart; Allison B. Coffin; David W. Crowder; E. Toby Kiers; Stephanie S. Porter (Evolutionary Applications)
ABSTRACT Successful plant growth requires plants to minimize harm from antagonists and maximize benefit from mutualists. However, these outcomes may be difficult to achieve simultaneously, since plant defenses activated in response to antagonists can compromise mutualism function, and plant resources allocated to defense may trade off with resources allocated to managing mutualists. Here, we investigate how antagonist attack affects plant ability to manage mutualists with sanctions, in which a plant rewards cooperative mutualists and/or punishes uncooperative mutualists. We studied interactions among wild and domesticated pea plants, pea aphids, an aphid‐vectored virus (Pea Enation Mosaic Virus, PEMV), and mutualistic rhizobial bacteria that fix nitrogen in root nodules. Using isogenic rhizobial strains that differ in their ability to fix nitrogen and express contrasting fluorescent proteins, we found that peas demonstrated sanctions in both singly‐infected nodules and mixed‐infection nodules containing both strains. However, the plant's ability to manage mutualists in mixed‐infection nodules traded off with its ability to defend against antagonists: when plants were attacked by aphids, they stopped sanctioning within mixed‐infection nodules, and plants that exerted stricter sanctions within nodules during aphid attack accumulated higher levels of the aphid‐vectored virus, PEMV. Our findings suggest that plants engaged in defense against antagonists suffer a reduced ability to select for the most beneficial symbionts in mixed‐infection tissues. Mixed‐infection tissues may be relatively common in this mutualism, and reduced plant sanctions in these tissues could provide a refuge for uncooperative mutualists and compromise the benefit that plants obtain from mutualistic symbionts during antagonist attack. Understanding the conflicting selective pressures plants face in complex biotic environments will be crucial for breeding crop varieties that can maximize benefits from mutualists even when they encounter antagonists.